The role of plum genotype in the inheritance of the trait of resistance to low negative temperatures - Vladimir S. Simonov; Yulia V. Burmenko (Аграрная наука Евро-Северо-Востока, 2021)
To assess the degree of inheritance in plum genotypes of the trait of resistance to the effects of damaging environmental factors of the cold season (after a thaw and after a thaw with subsequent hardening) and to identify forms with high resistance to low negative temperatures, in 2019-2020 an experiment on freezing under controlled conditions was set up (climatic chamber TH-6 (JEIO TECH, Korea)). The objects of the experiment were one-year shoots of seedlings of three hybrid families obtained as a result of controlled hybridization in 2016 (UB 8 × Smolinka, Kubanskaya Kometa × Utro, Kubanskaya Kometa × Smolinka), as well as parental varieties: Kubanskaya Kometa, Smolinka, Utro and hybrid UB 8 with various forms of field resistance to low negative temperatures (based on average long-term observations in 2007-2015) and with high indicators of agronomic valuable traits. For each component of the study of winter hardiness, the temperature regimes of freezing were selected: -22 °C for 15 hours after 5 days of thaw +3 °C (III component); -34 °C after 5 days of thaw and subsequent hardening at -5 °C within 5 days, then at -10 °C for 5 days (IV component). As a result of assessing the resistance of the hybrids to low negative temperatures, it was noted that after the thaw 73 % of the hybrids showed no damage; after a thaw followed by hardening, the total degree of freezing of hybrids varied from 0.5 points (UB 8 × Smolinka, form No. 10) to 4 points (UB 8 × Smolinka, form No. 4). Genotypes resistant to temperature changes from positive to negative with hardening from families UB 8 × Smolinka (forms No. 1, 10), Kubanskaya Kometa × Utro (form No. 3), Kubanskaya Kometa × Smolinka (form No. 2) are of interest for further breeding research. Assessment of the influence of the genome of parental forms on inheritance in hybrids of resistance to low negative temperatures according to component IV using the Spearman rank correlation method revealed an average direct insignificant correlation between winter hardiness in parental forms and hybrids.